The potential of nanobiopesticide based on zein nanoparticles and neem oil for enhanced control of agricultural pests - Pascoli, Mônica [UNESP]; de Albuquerque, Felícia Pereira [UNESP]; Calzavara, Anderson Kikuchi; Tinoco-Nunes, Bruno [UNESP]; Oliveira, Wanderson Henrique Cruz [UNESP]; Gonçalves, Kelly Cristina [UNESP]; Polanczyk, Ricardo Antônio [UNESP]; Vechia, Jaqueline Franciosi Della [UNESP]; de Matos, Sidnéia Terezinha Soares [UNESP]; de Andrade, Daniel Júnior [UNESP]; Oliveira, Halley Caixeta; Souza-Neto, Jayme A. [UNESP]; et al. (Springer Nature, 2020)
Nanomaterials composed of natural matrices associated with biopesticides have promising applications in sustainable agriculture. In this study, the biopesticide neem oil was encapsulated in zein nanoparticles in order to improve its stability and efficiency. Assays of phytotoxicity (using Phaseolus vulgaris) and biological activity against three pests (Acanthoscelides obtectus, Bemisia tabaci, and Tetranychus urticae) were also performed. The neem oil-loaded zein nanoparticles presented 198 ± 16 nm, polydispersity index of around 0.2, satisfactory physicochemical stability, together with high encapsulation efficiency (> 80%). Pre- and postemergence treatments using this new system did not cause any phytotoxic effects toward P. vulgaris. The neem oil nanobiopesticide exhibited mortality effects on B. tabaci and T. urticae, while the effect against A. obtectus was significantly increased, compared to plain neem oil. The results of the characterization, toxicity, and biological activity studies showed the promising potential of these neem oil-loaded zein nanoparticles for the use in pest management in sustainable agriculture after the required toxicological assessments.
Keywords: Azadirachtin; Biological activity; Nanoscale; Pest control; Phytotoxicity; Sustainable development